Social Media as a Digital Space for Online Gender-Based Violence (GBV) - Adelia Octavia Siswoyo; Ahmad Gimmy P. Siswadi (Pusat Studi Gender Universitas Jember, 2024)
Advances in technology and social media which are developing quite rapidly not only provide many positive benefits, but also trigger cyber crimes, one of which is online gender-based violence (KBGO) in the realm of social media. KBGO itself is a new form of gender- based violence that occurs due to the influence and assistance of technology. The purpose of this article aims to examine cases of KBGO in Indonesia that occur on social media and what are the rules and impacts of KBGO. The method in this study was carried out by studying the literature through searching related literature that has been published regarding KBGO that occurs on social media. The results found that reporting of KBGO cases in Indonesia in general has always increased every year. The increasing number of KBGO survivors and there are no regulations that significantly regulate KBGO, resulting in a loss of safe space for women to be able to use the internet, especially social media.